A review of the cicada genus Haphsa Distant from China (Hemiptera: Cicadidae) - Wang, Xu; Yang, Mingsheng; Wei, Cong (Zootaxa, 2015)
The cicada genus Haphsa Distant from China was reviewed based on the description of a new species (Haphsa lueta sp. n.) and redescriptions of other three known species which are reported from China for the first time. A key to all known species of Haphsa worldwide is provided. The geographical distribution of the Haphsa species and the availability of Haphsa dianensis Chou, Lei, Li, Lu & Yao, 1997 are discussed.